Development and Validation of the EmpathyScale in Marriage for Turkish Cultural Context - Şahin, Yahya Şahin; Şirin, Ahmet (My University, 2021)
The study aims to develop the scale of empathy in marriage. For the validity and reliability analysis of the scale, 638 data were collected from three different sample groups. To test the construct validity of the scale, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Criterion validity analysis were performed. Cronbach Alpha internal consistency coefficient was calculated for reliability. Result of the EFA indicated that the scale is one-dimensional and has good load values. The one-dimensional structure of the scale explains 50% of the total variance. Acceptable fit indices [?2/df = 2.977, RMSEA= .075, SRMR= 0.05, CFI= 0.954, RFI= 0.897, IFI= 0.954] was obtained in CFA. Criterion validity analysis shows that the scale has criterion validity (r= .472; p< .001). The Cronbach Alpha internal consistency coefficient (.876) of the scale shows that the reliability of the scale is high. The results obtained from the study show that the marital empathy scale is valid and reliable.
Keywords: Psikoloji; Aile Çalışmaları